Country stereotypes and L2 motivation: A study of French, German and Spanish language learners - Nikitina, L. (2015)
The purposes of this study (N=80) were: 1) to explore stereotypes about a target language (TL) country and TL learning motivation among beginner learners of French, German, and Spanish in a big public university in Malaysia, and 2) to examine whether there were relationships between the country stereotypes and the students’ motivation to learn a TL. To collect data, this study administered a questionnaire to the participants. To achieve the first research purpose, this study employed content analysis, which revealed that the respondents had diverse and overwhelmingly positive images about the TL countries. Interestingly, there were some differences in stereotype content across the three TL countries. For example, while technology-related images were prominent in the data collected from the learners of German, such references lacked among the images reported by the participants learning Spanish or French. As to the second research purpose, the findings of statistical analyses indicated that there were statistically significant and positive relationships between country stereotypes and TL learning motivation. The study concludes with discussing implications of the finding for L2 education.